THE EFFECT OF OWNERSHIP STRUCTURE ON TRANSFER PRICING OF MULTINATIONAL COMPANIES IN INDONESIA - B. T. Omenu, Roberto; Bayu Utomo, Rochmad (Universitas Mercu Buana Yogyakarta, 2024)
Transfer pricing practices have become a crucial issue in the world of taxation and finance of multinational companies. While transfer pricing remains lawful when adhering to the arm's length principle, numerous companies exploit regulatory gaps to strategically relocate profits toward jurisdictions with lower tax burdens. This research investigates the relationship between corporate ownership structures and transfer pricing behaviors, specifically examining four ownership categories: managerial, institutional, foreign, and family. The study employs a quantitative methodological approach, analyzing data collected from 24 multinational enterprises listed on the Indonesia Stock Exchange during the 2013-2024 timeframe, selected through purposive sampling methodology. Data analysis was conducted using SPSS Statistics, applying multiple linear regression analytical techniques. The findings demonstrate that managerial, foreign, and family ownership each independently exert positive and significant influences on transfer pricing practices. In contrast, institutional ownership shows no statistically significant impact. When assessed collectively, all four ownership structure variables demonstrate a significant combined effect on transfer pricing behaviors. The findings call for stricter tax oversight, especially for firms with certain ownership structures, and emphasize transparent governance and tax compliance.